Palladium Supported on Oleic Acid-coated Magnetic Nanoparticle as an Efficient Catalyst for Heck Coupling Reaction in Aqueous Media - Rafiee, Ezzat; Ataei, Ali; Joshaghani, Mohammad (Letters in Organic Chemistry, 2014)
A magnetically recoverable heterogeneous catalyst was synthesized by immobilization of Pd on the surface of oleic acid coated Fe3O4 nanoparticle. This catalyst was used for Heck coupling reaction of styrene with various aryl halides in aqueous media. The catalyst /product separation could be easily achieved with external magnetic field.
Keywords: magnetically nanoparticles